Mewujudkan Indonesia Maju: Korelasi dan Relevansi Pemikiran Sartono Kartodirdjo terhadap Konsep Politik Inspiratif Mahfud MD - Amin, Sifaul (Perkumpulan Program Studi Sejarah Se-Indonesia, 2025)
The purpose of this study is to analyze the relevance of Sartono Kartodirdjo's thoughts in the concept and practice of politics shown by Mahfud MD. This research method uses a qualitative method with a phenomenological approach. The results of the study show that realizing an advanced nation cannot be separated from the role of the thoughts of revolutionary and adaptive national figures. Sartono Kartodirdjo has the idea that in realizing an advanced and modern country, it cannot be separated from the five principles of life that must always be applied. Mahfud MD, as a national figure who currently still exists in the national arena, has thoughts about the concept of inspirational politics that are in line with Sartono Kartodirdjo's thoughts. Inspirational politics are politics that build justice, law enforcement, equality, and choose fair and honest leaders. The correlation and relevance of the thoughts of the two figures are important to study and apply to achieve common national goals. There is a close correlation and relationship between Sartono Kartodirdjo's thoughts about the five principles of life to realize an advanced nation and Mahfud MD's thoughts about inspirational politics. The thoughts of the two figures are also relevant to the current condition of the Indonesian nation, which requires united efforts in order to realize the nation's ideals of becoming an advanced nation.